Animal Models of Hirschsprung's Disease: State of the Art in Translating Experimental Research to the Bedside - Fujiwara, Naho; Nakazawa-Tanaka, Nana; Yamataka, Atsuyuki (European Journal of Pediatric Surgery, 2019)
Hirschsprung's disease (HSCR) is caused by incomplete colonization of enteric neural crest-derived cell (ENCC) in the bowel, the failure of ENCCs to proliferate, differentiate, and migrate leads to an absence of enteric neurons in the distal colon, resulting in colonic motility dysfunction. Various animal models of HSCR have been important in the understanding of the anatomy and pathophysiology of the disease and in the discovery of genes involved in HSCR. Four types of HSCR animal models have been developed: teratogen-induced, surgically created, naturally occurring models, and knockout models. Mutations in several genes affect enteric nervous system (ENS) development and can have pleiotropic effects on this system. Furthermore, certain animal models are informative regarding how such molecules control the development and functional differentiation of the ENS. In this article, we summarize recent advances in this field and highlight opportunities for new discoveries.
Keywords: animal models; Hirschsprung's disease; enteric nervous system; aganglionosis